Catalytic performance of CeAPSO-34 molecular sieve with various cerium content for methanol conversion to olefin - Sedighi, M. (Springer New York LLC, 2017)
A series of CeAPSO-34s with various cerium contents was synthesized and characterized by multiple techniques such as XRD, SEM, BET, 29Si MAS NMR, NH3-TPD and CO2-TPD. NH3-TPD spectra showed that a number of acid sites, especially those of strong acidity, is reduced with the increasing of Ce incorporation. Incorporation of metal ions gave rise to more silica-islands in the CeAPSO-34 framework. CO2-TPD showed that basic sites on the surface of modified samples are due to the presence of Ce-containing species incorporation into the framework of CeAPSO-34 molecular sieves. The performance of the catalysts was studied in methanol to olefin reactions at 425 °C under the atmospheric pressure. The results showed that the incorporation of cerium ions had great effects on the structure and acidity of the molecular sieves. All SAPO-34 and MeAPSO-34 molecular sieves were the very active and selective catalyst for light olefins production. Cerium incorporation improved the catalyst lifetime and favored the ethylene and propylene generation. However, an excess Ce content resulted in an inferior catalytic performance and stability. Therefore, there existed optimal cerium content for a specific SAPO-34. © 2017, Korean Institute of Chemical Engineers, Seoul, Korea.